Evolution of a seafloor massive sulfide deposit on axial volcanic ridges: a case study of the Duanqiao hydrothermal field, Southwest Indian Ridge - Weifang Yang; Chunhui Tao; Chunhui Tao; Shili Liao; Huichao Zhang; Huichao Zhang; Chuanwei Zhu; Wei Li; Guoyin Zhang; Xuefeng Wang; Lisheng Wang (Frontiers in Marine Science)
The mineralization process below the surface of the seafloor in a hydrothermal field has an important influence on the distribution and enrichment of elements. The Duanqiao hydrothermal field (DHF) is located on the new axial volcanic ridge of the ultraslow-spreading Southwest Indian Ridge. Owing to the limited surface sulfide samples, the metallogenic processes occurring below the seafloor surface such as the element enrichment mechanism and the temporal evolution of the sulfide deposits remain unclear. In this study, we conducted mineral texture, geochemical, 230Th/U dating, and laser ablation inductively coupled plasma mass spectrometer analyses of a drill core containing shallow sulfide deposits to study their evolution process. The results revealed that pyrite is enriched in Mn, Co, As, Mo, Ag, Cd, Sb, Tl, and Pb, chalcopyrite is characterized by high concentrations of Se, Sn, In, As, Ag and Pb, and sphalerite is enriched in Co, Ga, Ge, As, Ag, Cd, Sb, and Pb. The 230Th/U dating data suggested five different mineralization periods during 4,552–2,297 years. Apart from the top and bottom, the core exhibited obvious characteristics of gradual accumulation of mineralization. Results revealed that the variations in the elemental contents of different layers and different types of pyrite were controlled by the interaction of seawater and hydrothermal fluids within the sulfide mound over five different mineralization periods. Compared with other hydrothermal fields on other mid-ocean ridges, DHF pyrite is generally enriched in Zn, Pb, As, Ag, Cd, Mo, and Sb, which might reflect shallow subsurface mixing during different periods of hydrothermal activity.